2015
DOI: 10.1891/2158-0782.6.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Early Frenotomy Improves Breastfeeding Outcomes for Tongue-Tied Infants

Abstract: Although there is evidence to suggest that frenotomy improves breastfeeding outcomes for tongue-tied (ankyloglossic) infants, less is known about the optimal timing of treatment. In this retrospective cohort study, the timing of frenotomy and its impact on infant and maternal factors were examined in 31 tongue-tied babies with breastfeeding difficulties in a hospital in Jakarta, Indonesia. After frenotomy, all infants improved latching and mothers experienced a subjective improvement in nipple pain and breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Classes 3 and 4 lip-tie may contribute to breastfeeding problems and require revision (Kotlow, 2011). Similar to our population, Pransky, Lago, and Hong (2015) also reported frequent anterior and posterior tongue-ties, upper lip-ties, or their combinations, with upper lip-tie release improving breastfeeding in all cases.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Classes 3 and 4 lip-tie may contribute to breastfeeding problems and require revision (Kotlow, 2011). Similar to our population, Pransky, Lago, and Hong (2015) also reported frequent anterior and posterior tongue-ties, upper lip-ties, or their combinations, with upper lip-tie release improving breastfeeding in all cases.…”
Section: Discussionsupporting
confidence: 84%
“…Frenotomy, which describes the cutting of the lingual frenulum, has been shown to effectively resolve breastfeeding difficulties in infants with tongue-tie in clinical studies (Garbin et al, 2013;Kumar & Kalke, 2012). Early frenotomy in an infant during lactogenesis II prior to day 8 appears to have a larger impact on weight gain and lactation performance than late frenotomy after Day 8, which while improving latching, only results in small weight increases due to reduced maternal milk supply (Praborini, Purnamasari, Munandar, & Wulandari, 2015). Therefore, following frenotomy, we suggest a combinatorial treatment in a baby with nutritional problems and a mother with low milk supply consisting of supplementation with lactation aid, domperidone, and acupuncture.…”
mentioning
confidence: 99%
“…52 Once a mother has stopped breastfeeding, she will rarely restart, even if she has maintained her milk supply with pumping. The consensus group could not agree on a specific patient age where infant frenotomy would be most helpful but generally agreed with published studies advocating for early frenotomy, including infants who are \1 month of age [52][53][54] (Table 10).…”
Section: Frenotomy Indications and Informed Consentmentioning
confidence: 99%
“…They found that there was no difference in the total length of breastfeeding between groups that underwent frenotomy within the first week of life or after the first week of life, but there was a subjective benefit, as reported by the mother, in the infant’s ability to feed if frenotomy was performed within the first week of life. In a small study by Praborini et al, 30 it was found that infants who underwent frenotomy before 8 days of age gained significantly more weight than those infants who underwent frenotomy after 8 days. A retrospective study by Sharma and Jayaraj 31 found improved breastfeeding unrelated to whether division was before 30 days of age or after.…”
Section: Resultsmentioning
confidence: 95%